Sex Offender Recidivism Revisited: Review of Recent Meta-analyses on the Effects of Sex Offender Treatment. (January 2016) - Kim, Bitna; Benekos, Peter J.; Merlo, Alida V.
The effectiveness of sex offender treatment programs continues to generate misinformation and disagreement. Some literature reviews conclude that treatment does not reduce recidivism while others suggest that specific types of treatment may warrant optimism. The principal purpose of this study is to update the most recent meta-analyses of sex offender treatments and to compare the findings with an earlier study that reviewed the meta-analytic studies published from 1995 to 2002. More importantly, this study examines effect sizes across different age populations and effect sizes across various sex offender treatments. Results of this review of meta-analyses suggest that sex offender treatments can be considered as "proven" or at least "promising, " while age of participants and intervention type may influence the success of treatment for sex offenders. The implications of these findings include achieving a broader understanding of intervention moderators, applying such interventions to juvenile and adult offenders, and outlining future areas of research.